Efficacy of Multimodal Prehabilitation vs. Standard Care on Postoperative Morbidity and Quality of Life in Major Gastrointestinal Oncology Surgery: A Systematic Review and Meta-Analysis - Stephen William Soeseno; Made Agus Dwianthara Sueta (Open Access Indonesian Journal of Medical Reviews, 2026)
Major gastrointestinal oncology surgery induces profound physiological stress, precipitating a severe reduction in functional capacity and high rates of postoperative complications. Traditional perioperative pathways optimize intraoperative and postoperative care but systematically overlook preoperative functional reserves. A systematic review and meta-analysis were conducted in strict adherence to PRISMA guidelines. Systematic searches were executed across PubMed, Embase, Cochrane CENTRAL, and Scopus from database inception to March 2026. High-quality clinical trials evaluating multimodal prehabilitation against standard care in gastrointestinal cancer surgery were analyzed. Pooled odds ratios (OR) and standardized mean differences (SMD) with 95% Confidence Intervals (CI) were calculated using a random-effects model, with heterogeneity assessed via the $I^2$ statistic. Multimodal prehabilitation significantly reduced overall 30-day postoperative complications compared to standard care (OR 0.35, 95% CI: 0.18–0.69, p=0.010, $I^2$=42%). This was driven primarily by a striking decrease in Grade II pulmonary infections. Functional capacity was remarkably preserved; prehabilitated patients demonstrated statistically superior walking distances postoperatively (SMD 1.25, 95% CI: 0.95–1.55, p<0.001). Sarcopenic patients receiving targeted nutritional supplementation with beta-hydroxy beta-methylbutyrate exhibited sustained improvements in chair rise repetitions (Mean Difference 4.0, 95% CI: 2.5–5.5) and significant physiological remodeling of intramuscular adipose tissue. In conclusion, multimodal prehabilitation fundamentally alters the physiological trajectory of patients undergoing major gastrointestinal oncology surgery. By proactively mitigating surgical stress and attenuating catabolic decline, this intervention ensures superior functional restitution and minimizes short-term morbidity.